¿Es necesario modificar el Decreto Legislativo 1071? Comentario al Proyecto de Ley Nº 1088-2016-CR - Artieda Aramburú, Rafael (2020)
The modifications proposed by the Draft Legislation N° 1088-2016-CR will be discussed throughout the following article. Furthermore, the author present a series of arguments that support his conclusion as to why he considers that said Draft Legislation contravenes the international principles and standards that underlie the General Arbitration Law, and how it could even affect the proper functioning of said institution in our country.